Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.3950
|View full text |Cite
|
Sign up to set email alerts
|

AB0334 THE OVARIAN RESERVE MEASURING THE ANTI-MüLLERIAN HORMONE IS NOT DIMINISHED IN PATIENTS WITH RHEUMATOID ARTHRITISCOMPARED TO THE HEALTHY POPULATION

Abstract: BackgroundRheumatoid Arthritis (RA) is the most prevalent chronic inflammatory arthritis, affecting 0.5-1% worldwide population and predominates in females. Altered fertility has been reported due to a decrease in ovarian reserve secondary to sustained inflammation. The anti-Müllerian Hormone (AMH) is currently the most reliable biomarker of ovarian reserve. However, few and contradictory studies have been reported to analyze the relationship between fertility in RA women patients and AMH.ObjectivesThe aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is a complex interaction between RA disease and ovarian function. There were 2 studies that reported contradictory results of AMH levels in RA patients last year, which may be due to small size and different people [6,8]. Brouwer et al [6] conducted a longitudinal cohort and found a significant decline of AMH in female RA patients over time than expected, indicating that the chronic inflammatory may result in a faster de- In this meta-analysis, we estimated a pooled AMH levels SMD of −0.40 (95% CI: −0.66 to −0.14) in 679 RA patients and 1,460 controls providing a significant decline of AMH levels in RA patients, which confirmed the Brouwer et al [6] conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a complex interaction between RA disease and ovarian function. There were 2 studies that reported contradictory results of AMH levels in RA patients last year, which may be due to small size and different people [6,8]. Brouwer et al [6] conducted a longitudinal cohort and found a significant decline of AMH in female RA patients over time than expected, indicating that the chronic inflammatory may result in a faster de- In this meta-analysis, we estimated a pooled AMH levels SMD of −0.40 (95% CI: −0.66 to −0.14) in 679 RA patients and 1,460 controls providing a significant decline of AMH levels in RA patients, which confirmed the Brouwer et al [6] conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of AMH among women with RA have yielded inconsistent results and questionable association with fertility. Recently, some studies reported reduced AMH levels in patients with RA [6,7], whereas others found ovarian reserve determined by AMH was not diminished in RA patients [8,9]. Small sample sizes may result in contradictory results.…”
Section: Introductionmentioning
confidence: 99%